Generating Plasma by Cumulative Detonation in a Combustion Chamber - Jiří Šonský; Václav Tesař (International Journal of Aerospace Engineering)
All combustion processes in present-day engineering applications are of the deflagration type. This character limits achievable values of parameters, such as the highest reached temperature and the corresponding degree of gas ionisation. If it were possible to increase the parameter values and reach the plasmatic state, a number of potentially useful combustion applications might be improved—like propulsion or electricity generation. Authors demonstrate a combustion chamber with detonation-type combustion that can reach, by cumulative implosion, extreme temperatures of generated thermal plasma.